Peru : National Survey of Rural Household Energy Use - Meier, Peter (World Bank, Washington, DC, 2014)
The survey provided data on rural household energy use and expenditures, use by rural households of electricity from the grid, and use by rural households of off-grid electricity. The survey also provided information for an analysis of the economic benefits from electricity use in rural areas in Peru. Finally, the data were analyzed to provide implications for further development of rural electrification policies in Peru. It is important to note that the report represents the situation with respect to rural electrification in Peru in 2005-2006. The survey was initiated during the preparation of the World Bank-Global Environment Facility (GEF)-assisted Peru Rural Electrification Project. It provided socioeconomic and energy data to inform the design of the Project and also assist in improving policies for rural electrification in Peru. The preliminary data from the survey were used to prepare the economic and financial analysis for the Peru Rural Electrification Project. The main conclusion of the survey is that rural households in Peru have a significant desire, willingness, and ability to pay for electricity. Households without electricity from the grid frequently pay more for energy of lesser quality from kerosene lamps or batteries than they will pay for electricity service. However, the need to pay the connection cost is a significant barrier, and 25 percent of households living in areas with electricity service are not connected. Use of car batteries by 18 percent of rural households without electricity is a strong indication of unsatisfied demand for electricity in areas near to the grid. The survey report provides data for the planning of rural electrification in the context of Peru, including estimates of the benefits, which are particularly important for the economic analysis of projects. However, the authors believe that the survey report will also be useful to other countries as an example of a comprehensive effort to collect and analyze original data on rural household energy use.